Ideology and participation: examining the constitutional convention of 1787 - Gelman, David A. (2018)
This article looks at the effect of ideology on delegate participation at the Federal Convention of 1787. Making use of an original data set on delegate verbosity and delegate speeches at the Constitutional Convention, analysis reveals that ideologically extreme Convention delegates were more likely to participate at the Convention. This leads to two conclusions. First, ideology affected delegate participation in a meaningful way. Second, claims made about the intent of the writers of the Constitution based on Convention records are biased in favor of ideologically extreme Convention delegates, as extreme delegates were more likely to be recorded. - Reproduced.
Keywords: Constitutional law - U.S.A.